Reducing urban energy consumption and carbon emissions: a novel GIS-based model for sustainable spatial accessibility to local services and resources - Baran Rahmati; Hamidreza Rabiei-Dastjerdi; Simon Elias Bibri; Mohammad Ali Aghajani; Maryam Kazemi (Computational Urban Science)
Abstract This study explores the complex interconnections among global population growth, energy consumption, CO2 production, and disparities in service access through the lens of a single case study. Rapid population growth in many major cities has created significant challenges related to equitable access to services and socio-economic development, thereby impacting both their energy consumption patterns and environmental impacts. The case investigated in this study, like many other cases in developing countries, exhibits differences in service provision, infrastructure development, and energy usage, particularly between the northern and southern regions, which significantly affect the quality of life, environmental sustainability, and economic development. Previous efforts to narrow these geographic disparities have yielded limited success and exhibited several shortcomings. By employing a GIS Analytical Network Process method, this study examines service accessibility patterns in a single-case city, with a particular emphasis on green spaces, food services, and educational facilities and services. This GIS-based approach seeks to achieve sustainable levels of access to multiple land uses by evaluating their accessibility and identifying areas of overlap between them. The study endeavors to increase access and density of service standards when planning the placement of new facilities based on these standards in new locations. The method developed in this study represents a critical stride toward achieving these key objectives. The findings reveal that only 47% of city population blocks enjoy high service accessibility, while 40% have moderate accessibility, and 2.6% experience poor accessibility. These insights are of significant value to urban planners, researchers, and policymakers striving to reduce energy shortages and promote sustainable energy and transportation strategies to mitigate environmental impact in urban areas.